2012
DOI: 10.1007/s10896-012-9419-3
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Transmission of Intimate Partner Violence: Differentiating Correlates in a Random Community Sample

Abstract: The current study used a random sample of 502 men and women to investigate the intergenerational transmission of violence and assess the impact of family-oforigin violence on later adult intimate partner violence (IPV) perpetration and victimization while controlling for a host of theoretically-relevant factors and demographic characteristics. Six multivariate logistic regression analyses were modeled to identify differential correlates depending upon type of violence perpetration and victimization. Findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 85 publications
(114 reference statements)
3
63
0
1
Order By: Relevance
“…In their qualitative longitudinal study of 160 young people (73% female, 69% ethnic minorities) with confirmed experiences of sexual abuse as children, Feiring, Simon, Cleland, and Barrett (2013) found that stigmatisation and re-traumatisation from CSA can promote anger and violence within relationships in adolescence and adulthood. Furthermore research by Milletich et al (2010) and Franklin and Kercher (2012) showed that girls witnessing domestic violence and controlling behaviour within the family were more vulnerable to experiences of domestic violence in later life. Boys experiencing similar home circumstances however, were found by Laporte et al (2011) to be more likely to become the perpetrator of violence within their relationships.…”
Section: The Normalisation Of Sexual Relations With Childrenmentioning
confidence: 99%
“…In their qualitative longitudinal study of 160 young people (73% female, 69% ethnic minorities) with confirmed experiences of sexual abuse as children, Feiring, Simon, Cleland, and Barrett (2013) found that stigmatisation and re-traumatisation from CSA can promote anger and violence within relationships in adolescence and adulthood. Furthermore research by Milletich et al (2010) and Franklin and Kercher (2012) showed that girls witnessing domestic violence and controlling behaviour within the family were more vulnerable to experiences of domestic violence in later life. Boys experiencing similar home circumstances however, were found by Laporte et al (2011) to be more likely to become the perpetrator of violence within their relationships.…”
Section: The Normalisation Of Sexual Relations With Childrenmentioning
confidence: 99%
“…89 the results indicate anxious/insecure attachment styles that also further contribute to potentially hostile interactions with partners as adults (Franklin & Kercher, 2012).…”
Section: Implications For Practicementioning
confidence: 82%
“…Literature demonstrates that children who experience victimization, particularly by their caretakers, will also experience violence in interpersonal adult relationships (Banford, Brown, Ketring, & Mansfield, 2015;Franklin & Kercher, 2012). From a family-of-origin perspective, it is theorized that victimized children eventually learn to accept violence within relationships as appropriate and thus maladaptive emotional regulation strategies develop overtime due to feeling un-protected by caregivers (Franklin & Kercher, 2012).…”
Section: Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations